The quest for a common humanity human dignity and otherness in the religious traditions of the Mediterranean (Numen Book Series, 2011)
The worldview that all human beings belong to one big family has, in the history of religions, never been taken for granted. Moreover, human rights are a modern notion that should not be projected back onto the sacred texts of Judaism, Christianity, and Islam. However, from the Hellenistic period onwards one encounters the idea of human duties towards not only parents, neighbours and fellow citizens but to all human beings. This volume explores the development of this idea from Antiquity to the present time focussing on the \'other\' as \'neighbour, enemy, and infidel\', on the interpretation of the Biblical story of Abraham´s sacrifice and on ancient and modern ethical and legal implications of the concept of human dignity.